Resistência "knockdown" em mosquitos Aedes aegypti no Brasil e suas implicações no controle da dengue - Santos, Débora Naiara dos (Universidade Federal de São Carlos, 2021)
Dengue is an arbovirus that, since its introduction, represents a great problematic for world public health, mainly in Brazil, which presents a great difficulty in eradicating this disease. Its main vector, Aedes aegypti (Linnaeus, 1762), was disseminated to several locations, through the expansion of population by globalization, successfully adapting to the environment. The climatic conditions and the lack of commitment of the population collaborate for the great mosquito population growth and for the large number of reported cases. The rate of continuous growth over the years has consequently generate high costs for the economy. The absence of vaccines and the fast dengue transmission cycle make to control vector the most viable option to combat this disease. The National Dengue Control Program (PNCD) is a project implemented by the Federal Government that institutes strategies to prevent this disease, with chemical control as one of the main control methods. By frequent use of insecticides, mainly pyrethroids, which work by opening continued in the sodium and potassium channel (CNa) characterizing a period of hyperexcitation, followed by the death of the target pest, has generated pressure for the selection of mosquitoes resistant to this mechanism of action, a phenomenon known as “knockdown” resistance, in which there is an alteration in the amino acids that make up the protein chains present in CNa that do not allow the usual action of these insecticides, consequently reducing their effect on the body. This scenario of resistance is already present in all Brazilian regions, making the Vector Control Program, which have a preference for traditional methods, a real failure. With this, the present work, of literature review, has as objective provide information on the current scenario of Dengue in Brazil and the knockdown resistance to in order to guide new projects to curb the spread of this disease in the country.
Knockdown resistance in Aedes aegypti mosquitos in Brazil and its implications on dengue control
Keywords: Aedes aegypti; Resistência; Knockdown; Dengue; Brasil; Piretróides; DDT; CIENCIAS AGRARIAS; CIENCIAS BIOLOGICAS::ZOOLOGIA; CIENCIAS SOCIAIS APLICADAS::DEMOGRAFIA::POLITICA PUBLICA E POPULACAO